Patient-centered medical home for patients with complex congenital heart disease. Issue 5 (October 2015) - Fernandes, Susan M.; Sanders, Lee M.
<x xml:space="preserve">Abstract</x> Purpose of review Originally conceived by pediatricians as a model for the care of children with special healthcare needs, the 'patient-centered medical home' (PCMH) has been identified by the Affordable Care Act as a model for all future outpatient care delivery. Although few studies have demonstrated its efficacy in improving care for children with congenital heart disease (CHD), access to a PCMH is likely to improve CHD-patient outcomes, including global function and quality of life, while reducing healthcare costs. Recent findings To date, most patients with complex CHD have their care anchored in cardiology subspecialty-care clinics, which lack many of the attributes of a PCMH. Given that many of these patients have noncardiac morbidities, including neurocognitive impairment and multiorgan dysfunction, we believe such patients will benefit from a PCMH model of care based on primary care. Summary The PCMH based on primary care for patients with complex CHD could result in improved clinical outcomes, improved patient satisfaction and quality of life as well as decreased healthcare costs. Policy and practice reform are required to increase CHD-patient access to a PCMH, based on primary-care settings.